Preparation of Temozolomide-Loaded Nanoparticles for Glioblastoma Multiforme Targeting-Ideal Versus Reality - Chooi Yeng Lee; Ing Hong Ooi (MDPI AG, 2016)
Temozolomide (TMZ) is one of the most effective chemotherapeutic agents for glioblastoma multiforme, but the required high administration dose is accompanied by side effects. To overcome this problem and to further improve TMZ's efficacy, targeted delivery of TMZ by using polymeric nanoparticles has been explored. We synthesised the PLGA-PEG-FOL copolymer and attempted encapsulation of TMZ into PLGA-PEG-FOL nanoparticles using the emulsion solvent evaporation method and the nanoprecipitation method. Conjugation of PEG and FOL to PLGA has been reported to be able to increase the delivery of TMZ to the brain as well as targeting the glioma cells. However, despite making numerous modifications to these methods, the loading of TMZ in the nanoparticles only ranged between 0.2% and 2%, and the nanoparticles were between 400 nm and 600 nm in size after freeze-drying. We proceed with determining the release profile of TMZ in phosphate buffered saline (PBS). Our initial data indicated that TMZ was slowly released from the nanoparticles. The metabolite of TMZ rather than the parent compound was detected in PBS. Our study suggests that while PLGA-PEG-FOL can be used as a polymeric or encapsulation material for central delivery of TMZ, a practical and cost effective formulation method is still far from reach.